Contribution of the epididymis beyond fertilization: relevance of CRISP1 and CRISP3 for sperm DNA integrity and early embryo development - Sulzyk, Valeria (2024)
Numerous reports show that the epididymis plays a key role in the acquisition of sperm fertilizing ability but less information exists on its contribution to embryo development. Evidence from our laboratory showed that mammalian CRISP (Cysteine-Rich Secretory Proteins), known to be expressed in the epididymis, to regulate calcium (Ca2+) channels and to participate in fertilization, may also be relevant for embryo development. More specifically, we found that males with simultaneous mutations in Crisp1 and Crisp3 genes exhibited normal in vivo fertilization but impaired embryo development. In the present work, aimed to investigate the mechanisms underlying this reproductive phenotype, we observed that embryo development failure was not due to delayed fertilization as no differences in sperm transport within the female tract nor in in vivo fertilization were found shortly after mating. The observation that impaired embryo development was also found in eggs fertilized by epididymal sperm either after uterine insemination or in vitro fertilization, revealed that the defects were already present at epididymal level. Of note, eggs fertilized in vitro by mutant sperm exhibited impaired meiotic resumption not due to defects in Ca2+oscillations during egg activation, prompting us to examine potential sperm DNA defects. Interestingly, higher levels of both DNA fragmentation and intracellular Ca2+ were observed for mutant than for control epididymal sperm, supporting sperm DNA damage, likely linked to a Ca2+ dysregulation, as the main responsible for the early development failure of mutant males. Together, our results support the contribution of the epididymis beyond fertilization, identifying CRISP1 and CRISP3 as novel male factors relevant for DNA integrity and early embryo development. Given the existence of human functional homologues of CRISP and the incidence of DNA fragmentation in infertile men, we believe these findings not only provide relevant information on the impact of epididymal factors on embryonic development but will also contribute to a better understanding, diagnosis and treatment of human infertility.